Effect of Rocket (Eruca sativa) Extract on MRSA Growth and Proteome: Metabolic Adjustments in Plant-Based Media - Doulgeraki, Agapi I.; Efthimiou, Georgios; Paramithiotis, Spiros; Pappas, Katherine M.; Typas, Milton A.; Nychas, George-John (Frontiers in Microbiology, 2017)
The emergence of methicillin-resistant Staphylococcus aureus (MRSA) in food has provoked a great concern about the presence of MRSA in associated foodstuff. Although MRSA is often detected in various retailed meat products, it seems that food handlers are more strongly associated with this type of food contamination. Thus, it can be easily postulated that any food could be contaminated with this pathogen in an industrial environment or in household and cause food poisoning. To this direction, the effect of rocket (Eruca sativa) extract on MRSA growth and proteome was examined in the present study. This goal was achieved with the comparative study of the MRSA strain COL proteome, cultivated in rocket extract versus the standard Luria-Bertani growth medium. The obtained results showed that MRSA was able to grow in rocket extract. In addition, proteome analysis using 2-DE method showed that MRSA strain COL is taking advantage of the sugar-, lipid- and vitamin-rich substrate in the liquid rocket extract, although its growth was delayed in rocket extract compared to LB medium. This work could initiate further research about bacterial metabolism in plant-based media and defense mechanisms against plant-derived antibacterials.